“Memory Groups” of Macikai Camps and Their Characteristic Narratives - Stončius, Justas (History / Istorija, 2022)
Abstract. The article analyzes the memories of prisoners of war and civilians imprisoned in Nazi Germany Stammlager (Stalag) 331 (Stalag I C (Heydekrug) and Stalag Luft VI camps, the 184 Prisoner of War (POW) Camp of the NKVD and the 2652 Special POW Hospital, the Ministry of the Interior of the Lithuanian SSR (MVD) in Corrective Labour Colony Number 3. Based on the memoirs, the aim is to analyze the narratives formed by the memory (or memoirs) groups of the Macikai camps, summarizing their content and systematizing the plots that dominate them: conditions in prisons, relations with the management of the camps, attempts to escape, etc.